Continuous nebulised salbutamol and oral once a day prednisolone in status asthmaticus. Issue 4 (October 1993) - Singh, M; Kumar, L
Abstract : A trial was conducted of continuous nebulised salbutamol and oral once a day prednisolone in a group of 11 children with status asthmaticus (group A) and compared with a conventional protocol comprising aminophylline infusion and intravenous hydrocortisone every six hours in a matched control group (group B). Monitoring by a clinical asthma score, pulse oximetry (oxygen saturation, SaO2), and peak expiratory flow rate (PEFR) revealed earlier improvement in these parameters in group A. Significant differences in mean SaO2 values appeared after 12 and 18 hours respectively. Mean PEFR percentage values were higher in group A compared with group B. A larger number (9/11) of patients could be discharged from hospital within 24 hours in group A compared with group B where only 3/11 could be discharged. All patients recovered without any side effects. It is concluded that continuous nebulised salbutamol and oral once a day prednisolone is safe and effective in treatment of children with status asthmaticus.